Proyecto de factibilidad para la creación de la empresa de servicios de radiología para la ciudad de Ambato, provincia de Tungurahua - Erique Piedra, Walter Darío (2017)
The province of Tungurahua has a great economic development due to its strategic location in the Centre of the country, reason why the demand for all services, particularly medical, has increased. I must point out that the medical radiology is currently based on the diagnosis and prevention of diseases, making this service one of the most sought after by doctors. The present study seeks to determine the feasibility of the project to create a company of services of Radiology and Imaging for the city of Ambato, Tungurahua province, through market research. The work is initiated by 383 surveys aimed at people over the age of 19 in the city of Ambato. For existing in the city offer, eight medical centres which provide radiology services were analysed. The potential demand for the year 2016 would be of 116966 people; the real demand for this year will be of 64455; the annual average requirement per person is 2 services per year; and, the effective demand is 68291 studies for the first year. In terms of total existing supply of services of Radiology in the city of Ambato, 57375 studies a year, so there is an unsatisfied 10916 studies demand. The name of the company will be "Centre of Radiology diagnostic Ambato CERADIAM S.A.". Those products that offers the company are: services of ultrasound, x-ray digital, tomography and resonance magnetic. Advertising and promotion will have an approximate cost of $10 ' 314.00. The company will have an installed capacity of 9600 studies per year, while capacity used for the first year will be 80% of the installed capacity, with an increase of 5% a year until you reach 100%. The company will be located in the Av. The Capulies and street poetry, parish Atocha, Ambato canton, the city of the same name, in the province of Tungurahua. The company will be constituted as a society anomie, with a Capital subscribed of $10.000,00. The project has an investment of $1 ' 050' 731.72 dollars; 40.36% is financed with contributions from Member shareholders; and the 59.64% is funded with a direct credit granted by the trading house of medical equipment. The first year is expected to earn $ $574 ' 784.48 dollars from the sale of these services. The income statement and cash flow projected to 10 years, with the following financial indicators: range from $189 ' 524.56; IRR of 16.02% and with a cost of 1:4. The capital recover over a period of 8 years, 6 months and 28 days. Determines, which, under the conditions of the study, the project is viable and the implementation is recommended.